2023
DOI: 10.1002/agr.21839
|View full text |Cite
|
Sign up to set email alerts
|

Food companies' productivity dynamics: Exploring the role of intangible assets

Ryota Nakatani

Abstract: Food insecurity has risen amid economic recovery from the COVID‐19 pandemic. Food companies' productivity dynamics can be driven by intangible assets, financing, economies of scale, lifecycle, and technological convergence. We confront this by studying productivity drivers for detailed food manufacturing industries using cross‐country firm‐level panel data. The results show that intangible assets nonlinearly and heterogeneously affect productivity growth, and countries with fewer product market regulations dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…This is because federalism or revenue decentralization could jeopardize economies of scale of revenue administration (McAndrew 2018). Economies of scale are the situation in which an increase in size improves the productivity of services (Nakatani 2023b(Nakatani , 2023c. Indeed, Feld, Kirchgässner and Schaltegger (2010) found that the overall effect of revenue decentralization leads to fewer tax revenues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because federalism or revenue decentralization could jeopardize economies of scale of revenue administration (McAndrew 2018). Economies of scale are the situation in which an increase in size improves the productivity of services (Nakatani 2023b(Nakatani , 2023c. Indeed, Feld, Kirchgässner and Schaltegger (2010) found that the overall effect of revenue decentralization leads to fewer tax revenues.…”
Section: Literature Reviewmentioning
confidence: 99%